Highly Strong and Tough Double‐Crosslinked Hydrogel Electrolyte for Flexible Supercapacitors - Yudong Liu; Nan Lu; Fengya Liu; Ruiqi Na; Guibin Wang; Shaowei Guan; Prof. Fengqi Liu (ChemElectroChem)
Abstract Excellent mechanical properties are indispensable for the wide application of supercapacitors and various wearable devices. In this article, a novel double‐crosslinked hydrogel electrolyte (DC‐GPE) is prepared by the combination of the hydrophobic association of acrylamide with the amphiphilic monomer AEO‐9‐AC and the ionic complexation of acrylic acid with Fe3+ for the first time by a two‐step method. Owing to the dual energy dissipation network, the DC‐GPE exhibits an excellent tensile strength of up to 3.1 MPa, an elongation at break of more than 900 % and a toughness of 18.1 MJ m−3, which is far beyond the currently reported hydrogel electrolyte. Moreover, the ionic conductivity of the DC‐GPE achieves as high as 40.1 mS cm−1, which is 3 times higher than the corresponding LiClO4 solution electrolyte (12.3 mS cm−1). Besides, the activated carbon‐based supercapacitor assembled by the DC‐GPE shows excellent electrochemical performance, which is superior to most activated carbon‐based supercapacitors. These results demonstrate that the DC‐GPE shows a great application prospect in wearable devices like supercapacitors. Significantly, the new dual physical cross‐linking strategy improves the contradiction between the strength and the toughness of the gel electrolyte materials. And provides a new solution for preparing high‐strength as well as high‐toughness gel electrolyte.